SubsidyExplorer: A decision-support tool to improve our understanding of the ecological and economic effects of reforming fisheries subsidies - Millage, Katherine D.; Saccomanno, Vienna R.; Warham, Matthew M.; Rubino, Laura Lea; Schuhbauer, Anna; Sumaila, U. Rashid; Costello, Christopher (PLOS ONE, 2022)
The magnitude of subsidies provided to the fishing sector by governments worldwide is immense—an estimated $35.4 billion USD per year. The majority of these subsidies may be impeding efforts to sustainably manage fisheries by incentivizing overfishing and overcapacity. Recognizing the threat these subsidies pose, the World Trade Organization has set a goal of reaching an agreement that would end fisheries subsidies that contribute to overcapacity, overfishing, and illegal fishing. However, negotiations have been hampered by uncertainty around the likely effects of reforming these subsidies. Here we present a novel method for translating a bioeconomic model into an interactive online decision support tool that draws upon real-world data on fisheries subsidies and industrial fishing activity so users can directly compare the relative ambition levels of different subsidy reform options.